PENGARUH PEMBERIAN GULA PASIR DAN AIR KELAPA UNTUK MENINGKATKAN PERTUMBUHAN ANGGREK BULAN (Phalaenopsis hibrida) PASCA AKLIMATISASI.: Kata kunci: Anggrek bulan, air kelapa, dan gula pasir, panjang akar, jumlah daun saat terakhir. presentase hidup - Rika Sita Sari; Dewi Ratna Nurhayati; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
Research on “The effect of giving granulated sugar and coconut water to increase the growth of the moon orchid (Phalaenopsis hybrid)” was carried out from October 2022 to December 2022 at Sinoman Tempel, Sidorejo, Salatiga at an altitude of 500 maters above sea level. The aim of study was to determine the effect of the cococnut water and granulated sugar on the growth the phalaenopsis plant (Phalaenopsis hybrid). The research method used was factorial with a completely randomized desaign (RAL) which consisted of two factors and included 3 replications. The data from this study were analyzed using the BNJ test at the 5% level. Parameters observed included, The Last Number Of Leaves, Leaf Width, Leaf Length, Number Of New Leaves, Root Length, Growt Percentage. There are 2 research factors, namely the treatment of coconut water concentration (A) and granulated sugar (B). the results showed that 1) of coconut water has a significant effect on leaf number, leaf width root length and live presentation 2) Granulated sugar treatment had a significant effect on root length and live presentation 3)The interaction between the concentratios of coconut water and granulated sugar had a significant effect on root length, number of leaves at the last, and leaf width, 4) Giving the best treatment the treatment of 75 ml/L coconut water concentration and 30 gr granulated sugar (A3B3) which had a significant effect on parameters of root length, number ofleaves, and live percentage.